Análise do desempenho de estratégias de factor investing com baixa volatilidade e momentum em ações da B3 entre 2000 a 2022 - Gimenes, Gabriela Mendes (2024)
This dissertation explores the performance of Factor Investing strategies, focusing on the factors of low volatility and momentum, applied to B3 stocks from 2000 to 2022. The study underscores the effectiveness of these strategies amid the evolution of the investment universe, emphasizing the importance of fundamental theories and the growing complexity of financial markets. The results reveal that low volatility strategies consistently outperformed momentum strategies in terms of cumulative return, Sharpe Ratio, and standard deviation. In addition to contributing to investment decision-making, the research enriches financial literature by contextualizing the specific dynamics of the Brazilian stock market. The conclusion highlights a discrepancy in returns in the Brazilian market concerning the strategies discussed and benchmarks, suggesting potential relationships with the economic cycle and interest rates.